Relevance of Information Asymmetry Dividend Policy Models in Indian Context - Kapoor, Sujata (Indian Journal of Finance, 2007)
Dividend policy decision is one of the critical determinants of shareholders wealth. Thus, it is one of the most important decisions to be taken by a financial manager. Substantial literature in the field of corporate finance is available that discuss the impact of dividend decisions on shareholders wealth. This paper approaches dividend policy from the perspective of an interactive game between corporate mangers and shareholders. Recent theories suggest that dividend policy decisions carry concealed messages from management that may influence share prices. This paper is an attempt to review the literature and explore ways for shareholders to assess dividend policy and concludes Information asymmetry dividend models specifically Linter model is most relevant in Indian context.